The war on normal people : the truth about America's disappearing jobs and why universal basic income is our future - Yang, Andrew 1975- (Hachette Books, 2018)
From entrepreneur Andrew Yang, the founder of Venture for America, an eye-opening look at how new technologies are erasing millions of jobs before our eyes-and a rallying cry for the urgent steps America must take, including Universal Basic Income, to stabilize our economy.